2019
DOI: 10.1186/s40494-019-0294-6
|View full text |Cite
|
Sign up to set email alerts
|

Nano calcium carbonate versus nano calcium hydroxide in alcohols as a deacidification medium for lignocellulosic paper

Abstract: Deacidification is an established conservation treatment for the prolongation of the acidic paper stability. Several different deacidification systems are in use today, such as the dispersions of alkaline nanoparticles in organic solvents. The aim of the study was to compare the effects of different calcium nanoparticle dispersions in alcohols on lignocellulosic paper. Commercially available nano calcium hydroxide dispersions for paper deacidification, and laboratory prepared nano calcium carbonate dispersions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
9
0
2
Order By: Relevance
“…Based on those tables, the CIEDE2000 differences for each one of the four materials under study are shown graphically (Figure 3). In general, the color patches with inks printed upon them show a relatively slow degrading, with a barely steep slate, staying in most cases under the ∆E 00 CIEDE2000 < 1.5 threshold, implying a minimal perceivable color difference, only noticeable by trained eyes [25][26][27]. This indicates good stability and robustness in the considered exposition period.…”
Section: Resultsmentioning
confidence: 78%
“…Based on those tables, the CIEDE2000 differences for each one of the four materials under study are shown graphically (Figure 3). In general, the color patches with inks printed upon them show a relatively slow degrading, with a barely steep slate, staying in most cases under the ∆E 00 CIEDE2000 < 1.5 threshold, implying a minimal perceivable color difference, only noticeable by trained eyes [25][26][27]. This indicates good stability and robustness in the considered exposition period.…”
Section: Resultsmentioning
confidence: 78%
“…Bicchieri 等 [45] 考察了碳酸钙和丙酸钙纳米粒子在纸张 脱酸中的效果, 处理后纸张的 pH 值可提高 3~4 个单位. Malešič 等 [46] 将纳米碳酸钙(粒径约 100 nm)分别分散在 乙醇和异丙醇溶剂中制备浓度均为 0. 此外, 还有在所用溶剂中可以完全电离或者在低于 其饱和溶解度浓度下的可以形成均相溶液的离子形态 脱酸材料(表 2p~2t).…”
Section: 微纳米粒子形态脱酸材料unclassified
“…As emerging from the literature, the most promising morphology is represented by the nanosheets' morphology, which allows for not only the development of the alkaline reserve, but it also covers the paper fibers, acting as lamination sheet, as a first line of defense against acid attack from environmental sources [33]. Calcium and sodium carbonates are also common apparition in literature studies as sources of alkaline reserve [42,46].…”
Section: Impregnation Of Paper Samples In Nanocomposite Solutionmentioning
confidence: 99%